2012
DOI: 10.1161/strokeaha.111.641761
|View full text |Cite|
|
Sign up to set email alerts
|

Adiponectin and Carotid Intima-Media Thickness in the Northern Manhattan Study

Abstract: Background and purpose Adiponectin is an insulin-sensitizing plasma protein expressed in adipose tissue and suggested to play a role in atherosclerosis and cardiovascular disease. Data are lacking on the relationship between adiponectin and carotid intima-media thickness (IMT) in ethnically heterogeneous populations. We examined the relationship between adiponectin and IMT, a marker of atherosclerosis, in a multi-ethnic cohort study of stroke risk factors. Methods Participants were from the Northern Manhatta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 13 publications
2
34
0
Order By: Relevance
“…In postmenopausal women, Ogorodnikova et al found no evidence of an association between high molecular weight adiponectin levels and ischaemic stroke [19]. Secondly, several medications may affect ADP levels [30,31], but we could not pay attention to drug use. Another limitation of the study was the small sample size.…”
Section: Discussionmentioning
confidence: 85%
“…In postmenopausal women, Ogorodnikova et al found no evidence of an association between high molecular weight adiponectin levels and ischaemic stroke [19]. Secondly, several medications may affect ADP levels [30,31], but we could not pay attention to drug use. Another limitation of the study was the small sample size.…”
Section: Discussionmentioning
confidence: 85%
“…[4][5][6] Adiponectin levels were reduced in intracranial atherosclerosis versus other stroke etiologies 51 and correlated inversely with carotid intima media thickness. 52,53 Stroke continues to have a disproportionate impact on mortality for blacks compared to whites. 54,55 Incidence data from NOMAS have demonstrated race-ethnic differences in stroke incidence: Blacks had a 2.4-fold increased annual stroke incidence, and Hispanics a 2-fold increased annual stroke incidence compared to whites.…”
Section: Gardener Et Almentioning
confidence: 99%
“…In vivo studies performed in human aortic endothelial cells showed that adiponectin caused a dose-dependent decrease in adhesion molecules that regulate vascular inflammatory response, and lower adiponectin levels were associated with larger carotid artery intima-media thickness (12,13). However, a crosssectional study in patients with and without a previous history of ischemic cerebrovascular disease found an association between low adiponectin levels and ischemic cerebrovascular events (14).…”
Section: Discussionmentioning
confidence: 99%